Effect of additives on the synthesis efficiency of nanoparticles by laser-induced reduction - Rikuto Kuroda; Takahiro Nakamura; Hideki Ina; Shuhei Shibata (Beilstein Journal of Nanotechnology)
Laser-induced reduction in liquid (LRL) is a physicochemical technique for synthesizing nanoparticles by irradiating a solution containing metal ions with a high-intensity laser. It is simple and environmentally friendly, as it does not require reducing agents or high-temperature, high-pressure environments. In this method, nanoparticles are synthesized by reducing metal ions with short-lived radical species produced by the breakdown of solvent molecules in a high-intensity reaction field near the focus of the laser. This unique reaction has the characteristic of being able to synthesize non-equilibrium solid–solution alloy nanoparticles. On the other hand, it is necessary to improve the synthesis efficiency of nanoparticles in large quantities for practical use. In this study, we investigated improvements of the synthesis efficiency of nanoparticles in LRL by adding scavengers, such as isopropyl alcohol (IPA) and glycerin, for oxidative radicals formed by laser irradiation to the solution and converting the oxidative radicals into reducing species. Based on the evaluation of the synthesis efficiency of Au nanoparticles, it was confirmed that the addition of IPA increased the synthesis efficiency of nanoparticles by about five times, and the addition of glycerin increased it by about nine times. Furthermore, by adding these oxidizing radical scavengers, it became possible to synthesize nanoparticles even when the concentration of metal ions in the solution was increased. And as a result, the synthesis efficiency of nanoparticles increased by more than 18 times. This means that it is possible to synthesize 160 mg/h of Au nanoparticles in the current system. It was also shown that non-equilibrium solid–solution alloy nanoparticles could be synthesized even when a radical scavenger was added. Furthermore, the addition of a radical scavenger also made it possible to synthesize base metal nanoparticles, which have been difficult to synthesize using the LRL. In addition, the efficiency of nanoparticle synthesis has been dramatically improved, and the variety of materials that can be produced has increased. This expands the potential of nanoparticles synthesized by LRL to be used in industrial applications.